Carbon nanocoils decorated with scale-like mesoporous NiO nanosheets for ultrasensitive room temperature ppb-level NO2 sensing. Issue 4 (13th January 2023) - Sun, Yanming; Ding, Zhezhe; Zhang, Yupeng; Dong, Zhe; Sun, Lei; Wang, Neng; Yin, Meijie; Zhang, Jian; Wang, Guo Ping
Abstract : Although NO2 detection based on metal oxide semiconductors (MOSs) has received continuous attention, the sensing properties of MOSs still need to be further improved for practical application. Abstract : Although NO2 detection based on metal oxide semiconductors (MOSs) has received continuous attention, the sensing properties of MOSs still need to be further improved for practical application. Carbon nanocoils (CNCs) exhibit excellent physicochemical properties due to their unique polycrystalline amorphous structure and helical morphology. Herein, CNCs composited with NiO nanosheets were developed for room temperature NO2 sensing, in which highly dispersed mesoporous NiO nanosheets on CNCs was achieved with extremely higher sensitivity. Due to a large number of exposed active sites and the efficient conductive network of CNCs, this particular scale-like nanocomposite exhibits a nearly 8 times higher response to 60 ppm NO2 than bare NiO nanosheets at room temperature, outperforming the majority of previously reported NO2 sensors at room temperature. Moreover, the nanocomposite-based gas sensor has a detection concentration limit of 60.3 ppb, which is advantageous for the sensing of NO2 at low concentrations. We believe that this work will provide the direction for the research and development of highly sensitive smart sensors, as well as encourage further investigation of multifunctional sensing applications utilizing CNCs as the primary frame support material.